Su alcuni ritorni intertestuali nell’opera di Irit Amiel - Arsen Hordziy (Pl.it)
The article starts by briefly introducing Irit Amiel, one of the best known Polish-Israeli authors. The aspects of her biography relevant to her literary output are highlighted. The most conspicuous part of the text is dedicated to the discussion of intertextuality in Amiel’s works. First, it is presented in general terms with some examples of citation and allusion, followed by a more in-depth analysis of two of her works. It is argued that intertextuality shows a strong connection of Amiel to Polish literature, both before and after WWII, and gives significant insights to the interpretation of her work.